Improving the coverage of the top-wealth population in the Socio-Economic Panel (SOEP) - Carsten Schröder; Charlotte Bartels; Konstantin Göbler; Markus M. Grabka; Johannes König; Rainer Siegers; Sabine Zinn (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
We have developed and implemented a new sampling strategy to better represent very wealthy individuals in the German Socio-Economic Panel (SOEP). Our strategy is based on the empirical regularity that the very wealthy have at least part of their assets invested in businesses, and that businesses document shares of relevant shareholders in their books. Our results show that combined analysis of the SOEP and the new sample (SOEP-P) provides meaningful insights into individuals at the top end of the wealth distribution in Germany. The SOEP-P population has about 21 times higher net wealth on average than the regular SOEP population. Comparing millionaires (net worth 1M Euros) to the rest of the population, a number of noticeable differences emerge. Millionaires differ from the non-rich population with regard to portfolio allocation, demographics, careers, personality, satisfaction with life, and satisfaction with other important life domains.
Keywords: D31; D14; C83; 330; wealth distribution; oversampling; top wealth; wealth portfolios